A comparative study on different analysis approaches for estimating the axial loads on columns and structural walls at tall buildings. Issue 6 (21st March 2011) - Kurc, Ozgur; Lulec, Andac
SUMMARY: Estimating axial loads on columns and structural walls at tall buildings is a complicated task because time‐dependent deformations of concrete and the way the building is constructed affect the way the gravity loads are carried by them. The accurate computation of axial loads is crucial for determining the size and strengths of columns and structural walls. This study investigates several analysis approaches commonly used during the design of such buildings. Construction sequences, time‐dependent deformations and longitudinal reinforcement were considered, and their influences on results were discussed. A simplified model of an actual 37‐story building was used as a case study. The results indicated that the column and wall axial load might vary up to 45% depending on the type of analysis and effects that were considered. Copyright © 2011 John Wiley & Sons, Ltd.